Sandwich structure diaphragm coating material, preparation method and application thereof, and lithium ion battery

By preparing Bi@CNT-Al2O3@PDA composite separator coating material with a "sandwich" structure, the gas accumulation and safety hazards of lithium-ion batteries under overcharging and lithium dendrites are solved, and the battery performance and safety improvement is achieved.

CN119614066APending Publication Date: 2025-03-14华鼎国联动力电池有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411799384.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In practical applications, lithium-ion batteries have problems such as gas accumulation, electrical performance attenuation, and increased safety hazards, especially in the case of overcharge and lithium dendrites.

Method used

The Bi@CNT-Al2O3@PDA composite diaphragm coating material with a "sandwich" structure was prepared by chemical dealloyment method, vapor deposition method, hydrothermal synthesis method and self-assembly method. This material inhibits the growth of lithium dendrites through the introduction of nanometal Bi, the recombination of carbon nanotubes and nanoalumina increases the conductivity, and the amino functional groups in PDA reduce gas expansion.

Benefits of technology

It significantly improves the overall performance and safety of lithium-ion batteries, extends the battery's cycle life, and reduces the risk of battery explosion caused by gas accumulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614066A_ABST
    Figure CN119614066A_ABST
Patent Text Reader

Abstract

The invention relates to a sandwich structure diaphragm coating material, a preparation method and application thereof and a lithium ion battery, and relates to the technical field of lithium ion batteries, the preparation method comprises the following steps: taking a bismuth-containing alloy as a raw material, and adopting a chemical dealloying method to prepare nano metal bismuth particles; and depositing carbon nanotubes on the nano metal bismuth particles by adopting a vapor deposition method, an atomic layer deposition method, a spray pyrolysis method or a thermal chemical vapor deposition method to obtain Bi (at) CNT, and the like. According to the invention, a chemical dealloying method, a vapor deposition method, a hydrothermal synthesis method and a self-assembly method are adopted to finally obtain the Bi (at) CNT-Al2O3 (at) PDA composite material similar to a sandwich structure. The material has important application potential in the lithium ion battery, can effectively inhibit the growth of lithium dendrites, and improves the performance and safety of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a sandwich structure diaphragm coating material, a preparation method and application thereof, and a lithium ion battery. Background Art

[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles and energy storage systems due to their high energy density, long cycle life and low self-discharge rate. As an important component of lithium-ion batteries, the function and performance of the diaphragm directly affect the safety, efficiency and life of the battery. Lithium-ion batteries are mainly composed of the following parts: positive electrode, negative electrode, electrolyte and diaphragm. The diaphragm is located between the positive and negative electrodes. Its main functions include electrical isolation, ion conduction, thermal stability and mechanical strength. The diaphragm plays a vital role in lithium-ion batteries.

[0003] At present, the types of lithium-ion battery separators can be mainly divided into the following categories, including: ① Polymer separator. Polyethylene (PE) separator: It has excellent chemical stability and electrical insulation, and is often used in medium and low temperature environments. It has moderate porosity and good ionic conductivity. Polypropylene (PP) separator. It has high thermal stability and mechanical strength, and is often used in combination with PE separators to enhance the overall performance of the battery. Polyimide (PI) separator. It has good high temperature stability and excellent mechanical properties, and is suitable for use in high temperature environments. ② Ceramic separator. Ceramic separators are usually made of inorganic materials (such as alumina, silica, etc.) and have good thermal stability and mechanical strength. Ceramic separators perform well under extreme conditions and can improve the safety of batteries. ③ Composite separators. Composite separators are polymer-based materials combined with ceramics or nanomaterials to improve the mechanical strength, chemical stability and ionic conductivity of the separator. This type of separator is generally able to work better in high temperature and high voltage environments. ④ Porous membrane. Prepare membranes with a highly porous structure. This type of membrane is usually able to provide higher ionic conductivity and help improve the overall energy density of the battery. ⑤ Electrospinning nanofiber membranes. Nanofiber membranes prepared by electrospinning technology have high specific surface area and good ion conductivity. They allow faster ion transport and help improve the charging and discharging efficiency of the battery. ⑥ Smart membranes. This type of membrane usually has a temperature sensing function and can automatically close or change the pore structure when the temperature is too high to prevent the battery from overheating or short circuiting. Smart membranes are one of the important directions of future membrane research.

[0004] In the future, there are several possible directions for improving lithium-ion battery separators: ① Improve ion conductivity. Application of nanomaterials: By introducing conductive nanomaterials (such as carbon nanotubes or conductive polymers) into the separator, its ion conductivity can be improved, thereby increasing the charging rate. ② Highly conductive electrolyte coating: Coating highly conductive materials on the surface of the separator can improve the efficiency of interfacial ion conduction and reduce the resistance inside the battery. ③ Optimize pore size and porosity: Control pore size distribution: Design a separator with a larger average pore size or a specific pore size distribution to increase the migration speed of lithium ions and support fast charging. ④ Increase porosity: A separator with a porous structure can provide more channels and improve ion conduction efficiency, but the relationship between mechanical strength and porosity needs to be balanced. ⑤ Improve thermal stability: High temperature resistant materials: Develop separator materials with higher thermal stability (such as modified polyimide) to maintain structural stability during fast charging and prevent melting or deformation due to increased temperature. ⑥ Enhance mechanical strength: High-strength materials: Select or develop new materials with higher tensile strength and puncture strength to reduce the risk of breakage at high charging rates. ⑦ Composite material design: Use multilayer structures (such as a combination of inorganic coatings and polymer substrates) to improve the mechanical properties of the membrane while retaining good ionic conductivity.

[0005] At present, lithium-ion batteries often have the following obvious deficiencies in practical applications. The accumulation of gas will cause problems such as battery volume expansion and impedance increase, leading to electrical performance degradation. Combined with three-electrode data to monitor the data of the charging and discharging process of lithium iron phosphate (LFP) lithium soft-pack batteries. Gas generation: Excessive water will consume lithium salts and produce corrosive hydrogen fluoride, resulting in a decrease in capacity and increased safety hazards. Short circuit phenomenon: When lithium has an internal short circuit point, the local temperature rises sharply, causing the electrolyte to decompose. The accumulation of negative lithium dendrites produces a short circuit phenomenon. Overcharge effect: In the early stage of overcharge, the positive lithium element is not completely transferred, the oxidizability is low, and a small amount of carbon dioxide and olefins are produced. The decomposition of lithium compounds and the accumulation of negative lithium dendrites intensify the oxidation reaction, produce more carbon dioxide gas and cause the internal pressure to rise, causing the soft-pack aluminum-plastic film to expand. Summary of the invention

[0006] In order to solve the above problems, the present invention provides a sandwich structure diaphragm coating material and a preparation method and application thereof, and a lithium ion battery.

[0007] In a first aspect, the present invention provides a method for preparing a sandwich structure diaphragm coating material, the preparation method comprising the following steps:

[0008] Using bismuth-containing alloy as raw material, a chemical dealloying method is used to prepare nano-metal bismuth particles;

[0009] Depositing carbon nanotubes on the nano-metal bismuth particles by vapor deposition, atomic layer deposition, spray pyrolysis or thermal chemical vapor deposition to obtain Bi@CNT;

[0010] Aluminum oxide is loaded on the Bi@CNT by a hydrothermal synthesis method, a solvothermal method, a coprecipitation method, a microwave-assisted synthesis method or a supercritical fluid synthesis method to obtain Bi@CNT-Al2O3;

[0011] The Bi@CNT-Al2O3 and polydopamine are used as raw materials, and the sandwich structure diaphragm coating material is prepared by a self-assembly method.

[0012] Furthermore, the steps of preparing nano-sized bismuth metal particles by chemical dealloying method using bismuth-containing alloy as raw material include the following processes:

[0013] The aluminum-bismuth alloy is added into a strong alkaline solution, and then reacted at a temperature of 40 to 50° C. for 24 to 48 hours; the reactant is washed and dried to obtain the nano-metal bismuth particles.

[0014] Furthermore, the step of depositing carbon nanotubes on the nano-metal bismuth particles by vapor deposition includes the following process:

[0015] The nano-metal bismuth particles are reacted at a temperature of 550-650° C. with acetylene as a carbon source for 1-2 hours, and then cooled to room temperature to obtain the Bi@CNT.

[0016] Furthermore, the step of loading aluminum oxide on the Bi@CNT by a hydrothermal synthesis method includes the following process:

[0017] The Bi@CNT and aluminum chloride are added into water and stirred, and then hydrothermally synthesized at 180-250° C. for 8-10 hours. After the reaction is completed, the Bi@CNT is washed and dried to obtain aluminum oxide loaded on the Bi@CNT.

[0018] Furthermore, the weight ratio of the Bi@CNT to the aluminum chloride is (30-40):(60-80).

[0019] Furthermore, the step of preparing the sandwich structure diaphragm coating material by self-assembly method using the Bi@CNT-Al2O3 and polydopamine as raw materials includes the following process:

[0020] The Bi@CNT-Al2O3 and the polydopamine are added into water and dispersed by stirring, so as to form the sandwich structure diaphragm coating material through self-assembly.

[0021] Furthermore, the weight ratio of the Bi@CNT-Al2O3 and the polydopamine is (60-80):(60-80).

[0022] In a second aspect, the present invention provides a sandwich structure diaphragm coating material, wherein the sandwich structure diaphragm coating material is prepared by the preparation method described in any one of the first aspects.

[0023] In a third aspect, the present invention provides use of the sandwich structure diaphragm coating material prepared by the preparation method described in any one of the first aspect or the sandwich structure diaphragm coating material described in any one of the second aspect in the preparation of a lithium ion battery.

[0024] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the battery diaphragm material of the lithium-ion battery comprises the sandwich structure diaphragm coating material prepared by the preparation method described in any one of the first aspects or the sandwich structure diaphragm coating material described in any one of the second aspects.

[0025] The above technical solution provided by the embodiment of the present invention has at least the following advantages compared with the prior art:

[0026] The embodiment of the present invention provides a sandwich structure diaphragm coating material and its preparation method and application, and a lithium-ion battery. The present invention comprehensively uses chemical dealloying, vapor deposition, hydrothermal synthesis and self-assembly to successfully prepare a Bi@CNT-Al2O3@PDA composite diaphragm coating material with a "sandwich" structure. The material significantly enhances the affinity of lithium by introducing nano-metal Bi, thereby inhibiting the growth of lithium dendrites; and the composite of carbon nanotubes and nano-aluminum oxide improves the electrical conductivity and promotes the migration of lithium ions; at the same time, the gas adsorption capacity of amino groups in PDA effectively reduces the gas expansion of the battery cell. This new preparation scheme for diaphragm coating materials not only improves the overall performance of lithium-ion batteries, but also improves the safety of lithium-ion batteries. Specifically:

[0027] ①The role of nano-metal Bi

[0028] Inhibit the growth of lithium dendrites and improve safety performance. Lithium ions tend to adsorb on the Bi surface when the battery is charging, thus forming a lithium-philic alloy layer. The formation of this lithium-philic alloy layer helps the uniform deposition of lithium ions, thereby effectively inhibiting the growth of lithium dendrites. By controlling the particle size and distribution of Bi, the deposition path of lithium can be optimized, further improving the cycle performance of the battery. In addition, the alloying reaction between Bi and lithium can reduce the migration energy barrier of lithium, making the diffusion of lithium ions on the metal surface smoother, thereby accelerating the charge and discharge rate of the battery.

[0029] ②The role of carbon nanotubes loaded with nano-alumina

[0030] Enhance the conductivity of the coating material and improve the chemical stability. The functional design of carbon nanotubes (CNT) loaded with nano-aluminum trioxide (Al2O3) also plays a key role in improving the performance of lithium-ion batteries. As an excellent insulating material, the dispersion of nano-aluminum trioxide in the coating can effectively improve the overall mechanical strength and chemical stability. Carbon nanotubes have excellent conductivity, and their combination with Al2O3 can enhance the conductivity of the coating and promote good contact between the electrolyte and the diaphragm. Nano-aluminum trioxide has a micropore regulating effect. High-purity aluminum trioxide has a plate-like crystal structure. When the current is too large, the material heats up, and then the plate-like crystal structure of the nano-aluminum trioxide coating material will expand in volume, which will close the current conduction holes on the lithium battery diaphragm, thereby blocking the current. This greatly improves the safety performance of lithium batteries, thereby providing the possibility of high-energy safety and safe and reliable charging and discharging of high-power lithium batteries. Nano-aluminum trioxide also has very good thermal conductivity. When the battery temperature is too high, this material can conduct heat well, thus solving the problem of poor thermal conductivity of PP / PE materials. High-purity nano-aluminum oxide material also has excellent flame retardancy. Even if the temperature is too high and reaches the combustion threshold, the good flame retardancy of the material will prevent large-scale combustion or even explosion. Nano-high-purity aluminum oxide is used as a coating for lithium battery electrodes, which can effectively play a role in heat insulation and insulation, and improve safety performance.

[0031] ③ Gas adsorption of functional groups in PDA

[0032] Absorbs generated gas and reduces battery expansion. PDA contains abundant functional groups, especially amino groups, which react with Al 3+ The Al-O coordination bond formed can significantly improve the uniform flux of Li+. This uniform ion transport helps to reduce the migration barrier of lithium ions. During the cycle of lithium batteries, the battery cells may release some gases, such as hydrogen fluoride (HF) and carbon dioxide (CO2). The production of these gases will cause the battery cells to expand and even lead to battery failure. The amino functional groups in PDA have good gas adsorption capacity and can effectively adsorb these harmful gases, thereby reducing the flatulence problem of the battery cells. By introducing PDA into the diaphragm coating material, the material's ability to capture harmful gases can be improved, which reduces the risk of battery explosion caused by gas accumulation to a certain extent.

[0033] In summary, the present invention comprehensively utilizes a variety of advanced material preparation methods, namely chemical dealloying, vapor deposition, hydrothermal synthesis and self-assembly, and successfully develops a Bi@CNT-Al2O3@PDA composite diaphragm coating material with a "sandwich" structure. The introduction of nano-metal Bi significantly enhances the affinity of lithium, thereby inhibiting the growth of lithium dendrites; the composite of carbon nanotubes and nano-aluminum oxide improves the electrical conductivity and promotes the migration of lithium ions; at the same time, the gas adsorption capacity of amino groups in PDA effectively reduces gas expansion-related problems. The preparation scheme of this new diaphragm coating material not only improves the overall performance of lithium-ion batteries, but also ensures safety, providing new ideas and directions for the research and development of high-performance lithium batteries in the future. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0036] Figure 1 A schematic diagram of the process of preparing a sandwich structure diaphragm coating material according to an embodiment of the present invention. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0039] There are many coating materials for preparing lithium-ion battery separators. The following are some of the coating materials and their commonly used preparation methods:

[0040] Fluorinated polymer coating materials: have excellent chemical corrosion resistance and electrical insulation, and can improve the stability and safety of the diaphragm. Metal oxide coating materials: such as zinc oxide, tin oxide (. It can enhance the conductivity and thermal stability of the diaphragm, and can improve the performance of the diaphragm under high temperature conditions. Organic-inorganic composite coating materials: composite materials composed of organic polymers and inorganic nanomaterials (such as SiO2, TiO2, etc.). By combining the flexibility of organic polymers with the rigidity of inorganic materials, the comprehensive performance of the diaphragm, including mechanical strength and thermal stability, is improved. Conductive polymer coating materials: conductive polymers such as polyaniline and poly (3,4-ethylenedioxythiophene). Improve the conductivity of the diaphragm and improve the charge and discharge performance of the battery. Self-repair Coating materials: polymers with self-healing functions, such as polymers with dynamic bonds. When the membrane is damaged, its performance can be restored through self-healing function, extending the service life of the battery. Carbon-based composite coating materials: such as carbon black and graphene composite materials, which improve the conductivity and strength of the diaphragm, while also improving thermal stability and mechanical properties. Nanofiber coating materials: polymer nanofibers, which provide a larger specific surface area, improve the performance of the diaphragm, and enhance mechanical strength. These coating materials and methods all help to improve the performance of lithium-ion battery diaphragms, and the specific selection needs to take into account the cost, production process and required performance.

[0041] However, there are also some disadvantages in battery separator coating technology. Fluorinated polymer coating materials are prepared by solution coating, dipping or spraying. Disadvantages: high cost, difficult processing of polytetrafluoroethylene, and performance may be reduced at high temperatures. Metal oxide coating materials are often prepared by sol-gel method, vapor deposition (CVD), etc. Disadvantages: the coating may crack or peel off at high temperatures, and the uniformity and adhesion of the coating may be affected. Organic-inorganic composite coating materials are usually prepared by solution mixing method, layer-by-layer self-assembly method, etc. Disadvantages: the stability and interfacial compatibility of the composite material may be limited, and the cost and preparation process are complicated. Conductive polymer coating materials use electrochemical polymerization, solution polymerization or spraying method. Disadvantages: The environmental stability of conductive polymers is poor, it may decay over time, and the conductivity may be affected by factors such as humidity and temperature. Carbon-based composite coating materials combine carbon black or graphene with polymers by mechanical mixing, solution coating and other methods. Disadvantages: The poor dispersibility of carbon-based materials may lead to uneven performance, and high concentrations of carbon materials may increase the brittleness of the material. Preparation method of nanofiber coating material: polymer nanofibers are prepared by electrospinning.

[0042] Disadvantages: The nanofiber preparation process may lead to low production efficiency. The selection of suitable coating materials requires a comprehensive consideration of cost, performance, production process and application requirements. Various materials have their own limitations and challenges while improving the performance of lithium-ion battery separators. The following are some of the main disadvantages of lithium-ion battery separator applications: ① Insufficient thermal stability: Some polymer separators are prone to warping or melting at high temperatures, which may cause battery short circuits and failures. ② Chemical compatibility issues: The chemical compatibility of the separator material with the electrolyte is poor, which may cause the separator to degrade or affect battery performance. ③ Porosity and conductivity: The porosity and conductivity of the separator affect the ion conduction efficiency, limiting the high-rate discharge capacity and charging rate of the battery. ④ Insufficient mechanical strength: Some separators have low mechanical strength and may be squeezed during charging and discharging, resulting in breakage or short circuits. ⑤ Poor electrolyte permeability: The permeability of the separator may cause the electrolyte to leak in some cases, affecting the safety and stability of the battery.

[0043] The technical solution provided by the present invention is as follows:

[0044] In a first aspect, the present invention provides a method for preparing a sandwich structure diaphragm coating material, the preparation method comprising the following steps:

[0045] Using bismuth-containing alloy as raw material, a chemical dealloying method is used to prepare nano-metal bismuth particles;

[0046] Depositing carbon nanotubes on the nano-metal bismuth particles by vapor deposition, atomic layer deposition, spray pyrolysis or thermal chemical vapor deposition to obtain Bi@CNT;

[0047] Aluminum oxide is loaded on the Bi@CNT by a hydrothermal synthesis method, a solvothermal method, a coprecipitation method, a microwave-assisted synthesis method or a supercritical fluid synthesis method to obtain Bi@CNT-Al2O3;

[0048] The Bi@CNT-Al2O3 and polydopamine are used as raw materials, and the sandwich structure diaphragm coating material is prepared by a self-assembly method.

[0049] The embodiment of the present invention provides a method for preparing a sandwich structure diaphragm coating material, which is mainly used to improve the performance and safety of lithium-ion batteries. By comprehensively adopting chemical dealloying, vapor deposition, hydrothermal synthesis and self-assembly, a Bi@CNT-Al2O3@PDA composite material with a "sandwich" structure is successfully developed. The core components of the material include nano-metal Bi, CNT-Al2O3 and PDA, which combine to exert a significant material synergistic effect. First, Bi can effectively inhibit the growth of lithium dendrites, and this feature significantly improves safety during battery charging and discharging. The affinity alloy layer formed between Bi and lithium promotes the uniform deposition of lithium ions, reduces the risk of dendrite formation, and thus prolongs the cycle life of the battery. Secondly, the composite design of carbon nanotubes and nano-aluminum trioxide significantly improves the conductivity and enhances the mechanical strength and chemical stability of the diaphragm. Nano-aluminum trioxide is not only an insulating material, but also a good conductive material, which increases the ion conductivity of the material. Its microporous structure adjustment can close the current conduction holes on the lithium battery diaphragm when the current is too large, thereby effectively blocking the current and improving the safety of the battery. Finally, the amino functional groups rich in PDA show good gas adsorption capacity and can effectively capture harmful gases that may be released during the cycle of lithium batteries, such as hydrogen fluoride and carbon dioxide. The accumulation of these gases may cause battery cell expansion and battery failure, and the introduction of PDA significantly reduces such problems, thereby reducing the risk of battery explosion. Bi@CNT-Al2O3@PDA composite diaphragm coating materials have improved the overall performance and safety of lithium-ion batteries through a variety of advanced preparation technologies, providing new ideas and directions for the research and development and application of high-performance lithium batteries in the future, and making up for the shortcomings of existing technologies. Specifically:

[0050] (1) A Bi@CNT-Al2O3@PDA composite diaphragm coating material with a "sandwich" structure was prepared. The sandwich structure design is conducive to combining the synergistic effects between different materials. It effectively inhibits the growth of lithium dendrites, improves the conductivity of the coating material, and promotes the migration of lithium ions; at the same time, it reduces the problem of battery cell expansion caused by gas production during the cycle of lithium-ion batteries.

[0051] (2) A lithium-ion battery separator coating material is prepared by selecting such raw materials and such methods, and in particular, relates to a preparation method. The present invention sequentially combines metal Bi, CNT-Al2O3 and PDA through chemical dealloying, vapor deposition, hydrothermal synthesis and self-assembly to prepare a new type of Bi@CNT-Al2O3@PDA separator coating material with a sandwich structure, and then evenly coats the material on a lithium-ion separator polyethylene (PE) by spraying to prepare a new type of separator coating.

[0052] (3) The application of lithium-ion battery separator coating materials prepared in this way in lithium-ion batteries. Mainly including the application of Bi@CNT-Al2O3@PDA new separator coating material in lithium-ion power battery separators

[0053] In some specific embodiments, Figure 1 As shown, a method for preparing a novel lithium-ion battery separator coating material with a sandwich structure is provided, which specifically includes the following detailed steps:

[0054] S1: Preparation of nano-sized bismuth (Bi) particles by chemical dealloying. Take 100-200 mg of aluminum-bismuth alloy (Al 90 Bi 10 ) Add 50-60 mL of 2-4 mol / L potassium hydroxide (KOH) solution into a beaker, heat in a water bath at 40-50° C., and react for 24-48 hours. Wash and dry the reactants to obtain nano-sized bismuth (Bi) particles.

[0055] S2: Preparation of nano-metal bismuth-on-carbon nanotubes by vapor deposition. Take 50-60 mg of the metal bismuth (Bi) particle powder in step S1 above and place it in a reaction porcelain boat, put it in a tube furnace, use acetylene as the carbon source, the gas flow rate is 300-400 sccm, the reaction temperature is 550-650°C, and the reaction time is 1-2 hours. After cooling to room temperature, nano-metal bismuth-on-carbon nanotubes (Bi@CNT) can be obtained.

[0056] S3: Preparation of carbon nanotube-loaded aluminum oxide (Bi@CNT-Al2O3) by hydrothermal synthesis. Take 30-40 mg Bi@CNT and 60-80 mg aluminum chloride in a beaker, add 80-100 mL deionized water, mix and stir for 30-60 minutes to form a mixed and evenly dispersed solution. Transfer the solution to the inner tank of the reactor and perform hydrothermal synthesis at a temperature of 180-250°C for 8-10 hours. After the reaction is completed, wash and dry to obtain metallic bismuth and carbon nanotube-loaded aluminum oxide (Bi@CNT-Al2O3).

[0057] S4: Preparation of a new type of sandwich coating material (Bi@CNT-Al2O3@PDA) with polydopamine (PDA) coated with Bi@CNT-Al2O3 by self-assembly. Add 60-80 mg Bi@CNT-Al2O3 and 60-80 mg polydopamine (PDA) obtained in S3 to 150-250 mL of deionized water and mix them for 1-2 hours with ultrasonic dispersion. The functional group hydroxyl group in PDA can react with Al 3+Al-O coordination bonds are formed, thereby forming Bi@CNT-Al2O3@PDA through self-assembly, that is, it is divided into three layers including metal Bi, CNT-Al2O3 and PDA, that is, a new type of membrane coating material similar to a sandwich structure. The Bi@CNT-Al2O3@PDA coating material is evenly coated on the lithium ion membrane polyethylene (PE) by spraying, and the thickness of the coating is 5 to 15um. The coated lithium ion membrane is dried to remove the solvent. The membrane is baked at a temperature of 30 to 45°C so that the Bi@CNT-Al2O3@PDA coating material adheres to the membrane to form a stable coating.

[0058] Accordingly, a method for preparing a lithium ion battery as described below comprises the following steps:

[0059] S1': preparing positive and negative electrode slurries for lithium-ion batteries respectively, wherein the slurry components include positive and negative electrode materials, a binder, a thickener and a conductive agent.

[0060] Preferably, in the lithium-ion battery positive electrode slurry composition, the positive electrode material is lithium iron phosphate positive electrode material, the adhesive is polyvinylidene fluoride, and the conductive agent is conductive carbon black.

[0061] Preferably, in the negative electrode slurry composition of the lithium ion battery, the binder is styrene-butadiene rubber, the thickener is sodium carboxymethyl cellulose, the negative electrode material is graphite, and the conductive agent is conductive carbon black.

[0062] S2': A positive electrode and a negative electrode of a lithium-ion battery, which are prepared by coating the positive and negative electrode slurries on the positive electrode and negative electrode current collectors respectively.

[0063] Preferably, the positive electrode current collector is aluminum foil, and the negative electrode current collector is copper foil.

[0064] Preferably, the method for preparing the positive and negative electrode sheets of a lithium-ion battery comprises coating the positive and negative electrode slurries on the positive and negative electrode current collectors respectively, and performing rolling, slitting, die-cutting and baking to prepare the sheets.

[0065] S3': A lithium-ion battery, which is produced by laminating, packaging, injecting, wetting, forming, degassing, aging, capacity testing and sorting the positive and negative electrodes of the lithium-ion battery.

[0066] Preferably, the lithium-ion battery comprises an electrolyte, a separator, a shell, and a positive electrode and a negative electrode of the lithium-ion battery.

[0067] Preferably, the positive electrode and negative electrode of the lithium ion battery are separated by a diaphragm, and the electrolyte diaphragm and the positive electrode and negative electrode of the lithium ion battery are located inside the shell. The coating of the diaphragm is the novel coating material prepared in the present invention.

[0068] Preferably, the lithium-ion battery is a three-electrode soft pack, a square soft pack or a square shell.

[0069] A positive electrode slurry for a lithium-ion battery includes a solid component and a solvent. The solid component includes a positive electrode material, an adhesive and a conductive agent. The mass percentages are respectively 96-98% of the positive electrode material, 1-2% of the adhesive and 1-2% of the conductive agent.

[0070] A negative electrode slurry for a lithium-ion battery includes a solid component and a solvent. The solid component includes a negative electrode material, an adhesive, a thickener, and a conductive agent. The mass percentages are respectively negative electrode material (94-97%), adhesive (1-2%), thickener (1-2%), and conductive agent (1-2%).

[0071] The positive electrode sheet of a lithium-ion battery is prepared by coating the positive electrode slurry of the lithium-ion battery on the positive electrode aluminum foil current collector, and then rolling, slitting, die-cutting and baking. The positive electrode slurry includes solid components and solvents. The solid components include positive electrode materials, adhesives and conductive agents.

[0072] The negative electrode sheet of a lithium-ion battery is prepared by coating the negative electrode slurry of the lithium-ion battery on the negative electrode copper foil current collector, and then rolling, slitting, die-cutting and baking. The negative electrode slurry includes solid components and solvents. The solid components include negative electrode materials, adhesives and thickeners.

[0073] A lithium-ion battery comprises a positive electrode, a negative electrode, an electrolyte, a separator and a shell. The positive electrode is prepared by coating a positive electrode slurry on an aluminum foil current collector, wherein the positive electrode slurry comprises a solid component and a solvent. The solid component comprises a positive electrode material, an adhesive and a conductive agent. The negative electrode slurry comprises a solid component and a solvent. The solid component comprises a negative electrode material, an adhesive, a thickener and a conductive agent.

[0074] It should be noted that the sandwich structure diaphragm coating material and its preparation method and application, and the component raw materials involved in the lithium-ion battery provided in the embodiments of the present invention, unless otherwise specified or specified, can directly adopt commercially available products or adopt existing public preparation methods to make them by themselves; at the same time, the steps and parameters involved, unless otherwise specified or specified, can be carried out according to existing processing technology or directly carried out using existing equipment, and the present invention document will not elaborate on them one by one.

[0075] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0076] Example 1

[0077] This example provides a sandwich structure diaphragm coating material and applies it to the preparation of lithium-ion batteries, specifically including the following processes:

[0078] (1) Take 100 mg of aluminum-bismuth alloy (Al 90 Bi 10 ) Add 50 mL of 2 mol / L potassium hydroxide (KOH) solution into a beaker, heat in a water bath at 40°C, and react for 24 hours. Wash and dry the reactants to obtain nano-sized bismuth (Bi) particles.

[0079] Secondly, take 50mg of metal bismuth (Bi) particle powder in a reaction porcelain boat, put it into a tube furnace, use acetylene as a carbon source, the gas flow rate is 300sccm, the reaction temperature is 600℃, and the reaction time is 1.5h. After cooling to room temperature, carbon nanotubes deposited on nano-metal bismuth (Bi@CNT) can be obtained.

[0080] Next, take 30 mg Bi@CNT and 60 mg aluminum chloride in a beaker, add 80 mL deionized water, mix and stir for 30 minutes to form a mixed and evenly dispersed solution. Transfer the solution to the inner tank of the reactor and perform hydrothermal synthesis at a temperature of 180°C for 8 hours. After the reaction is completed, wash and dry to obtain metallic bismuth and carbon nanotube-loaded aluminum oxide (Bi@CNT-Al2O3)

[0081] Finally, 60 mg Bi@CNT-Al2O3 and 60 mg polydopamine (PDA) were added to 200 mL deionized water and mixed and ultrasonically dispersed for 1 h. The functional groups of PDA can react with Al 3+ Al-O coordination bonds are formed, thereby forming Bi@CNT-Al2O3@PDA through self-assembly, that is, it is divided into three layers including metal Bi, CNT-Al2O3 and PDA, that is, a new type of membrane coating material similar to a sandwich structure. The Bi@CNT-Al2O3@PDA coating material is evenly coated on the lithium ion membrane polyethylene (PE) by spraying, and the coating thickness is 5um. The coated lithium ion membrane is dried to remove the solvent. The membrane is baked at 30°C so that the Bi@CNT-Al2O3@PDA coating material adheres to the membrane to form a stable coating.

[0082] (2) Dissolve 100g of polyvinylidene fluoride (PVDF) in N-methylpyrrolidone (NMP) solvent, and then add lithium iron phosphate (LiFePO4) positive electrode material and conductive agent conductive carbon black and mix them evenly. Among them, the lithium-ion battery positive electrode slurry is LiFePO4 (98%), PVDF (1%) and conductive agent (1%) according to weight percentage. Dissolve 100g of sodium carboxymethyl cellulose (CMC) in deionized water, and then add negative electrode material graphite, conductive agent graphene-loaded lithium carbon nanotubes, and styrene-butadiene rubber (SBR) and mix them evenly. Among them, the lithium-ion battery negative electrode slurry is graphite negative electrode material (97%), conductive agent conductive carbon black (1%), CMC (1%) and SBR (1%) according to weight percentage.

[0083] (3) The obtained positive electrode slurry of lithium-ion battery is coated on the aluminum foil current collector, and the negative electrode slurry is coated on the copper foil current collector. Finally, the positive and negative electrode sheets are produced by rolling, slitting, die-cutting and baking.

[0084] (4) Assemble the positive and negative electrode sheets in step (3) with a separator, an electrolyte and a shell into a lithium-ion battery. The separator is polyethylene (PE), and the coating of the separator is Bi@CNT-Al2O3@PDA material attached to the separator to form a stable coating.

[0085] Example 2

[0086] This example provides a sandwich structure diaphragm coating material and applies it to the preparation of lithium-ion batteries. The only difference from Example 1 is that only the vapor deposition time is changed to 1 hour; the other steps and parameters are the same.

[0087] Example 3

[0088] This example provides a sandwich structure diaphragm coating material and applies it to the preparation of lithium-ion batteries. The only difference from Example 1 is that only the vapor deposition time is changed to 2 hours; the remaining steps and parameters are the same.

[0089] Comparative Example 1

[0090] This example provides a lithium-ion battery, which differs from Example 1 only in that the battery separator is replaced with a separator made of polyethylene (PE) without a coating material.

[0091] Comparative Example 2

[0092] This example provides a lithium-ion battery, which is different from Example 1 only in that the battery separator is replaced with polypropylene (PP) and there is no coating material.

[0093] Comparative Example 3

[0094] This example provides a lithium-ion battery, which differs from Example 1 only in that the sandwich structure diaphragm coating material is replaced with Ti@CNT-Al2O3@PDA ("Bi" is replaced with the commonly used "Ti" according to the preparation method in Example 1).

[0095] Comparative Example 4

[0096] This example provides a lithium-ion battery, which differs from Example 1 only in that the sandwich structure diaphragm coating material is replaced with Si@CNT-Al2O3@PDA ("Bi" is replaced with the commonly used "Si" according to the preparation method in Example 1).

[0097] Test Case

[0098] In this example, when the negative electrode materials in the above embodiments and comparative examples are applied to lithium-ion batteries, the puncture strength of the diaphragm before and after the test, the gas production of the lithium-ion battery, the internal resistance of the lithium-ion battery, the 2C rate charge, the 3C rate discharge, and the room temperature cycle retention rate are compared as shown in Table 1.

[0099] Table 1

[0100]

[0101]

[0102] As can be seen from Table 1, by testing the puncture strength of the diaphragm, the gas production of the lithium-ion battery, the internal resistance of the lithium-ion battery, the 2C rate charge, the 3C rate discharge, and the room temperature cycle retention rate, the lithium-ion battery diaphragm coating material of Example 1 has good properties. It is mainly manifested in that the performance of the test items of the puncture strength of the diaphragm, the gas production of the lithium-ion battery, the internal resistance of the lithium-ion battery, the 2C rate charge, the 3C rate discharge, and the room temperature cycle retention rate are all higher than those of Example 2, Example 3, Comparative Example 1 and Comparative Example 2. The results show that the Bi@CNT-Al2O3@PDA composite diaphragm coating material with a "sandwich" structure prepared by the present invention has good puncture strength of the diaphragm and can improve the safety performance of lithium-ion batteries. The material significantly enhances the affinity of lithium by introducing nano-metal Bi, thereby inhibiting the growth of lithium dendrites; the composite of carbon nanotubes and nano-aluminum oxide improves the conductivity and promotes the migration of lithium ions, which is beneficial for lithium-ion batteries to perform better at high rates. The gas adsorption capacity of amino groups in PDA effectively reduces the expansion of the battery cell and improves the cycle stability of lithium-ion batteries.

[0103] Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0104] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A method for preparing a sandwich structure diaphragm coating material, characterized in that: The preparation method comprises the following steps: Using bismuth-containing alloy as raw material, a chemical dealloying method is used to prepare nano-metal bismuth particles; Depositing carbon nanotubes on the nano-metal bismuth particles by vapor deposition, atomic layer deposition, spray pyrolysis or thermal chemical vapor deposition to obtain Bi@CNT; Aluminum oxide is loaded on the Bi@CNT by a hydrothermal synthesis method, a solvothermal method, a coprecipitation method, a microwave-assisted synthesis method or a supercritical fluid synthesis method to obtain Bi@CNT-Al2O3; The Bi@CNT-Al2O3 and polydopamine are used as raw materials, and the sandwich structure diaphragm coating material is prepared by a self-assembly method.

2. The method for preparing the sandwich structure diaphragm coating material according to claim 1, characterized in that: The steps of preparing nano-sized bismuth metal particles by chemical dealloying method using bismuth-containing alloy as raw material include the following processes: The aluminum-bismuth alloy is added into a strong alkaline solution, and then reacted at a temperature of 40 to 50° C. for 24 to 48 hours; the reactant is washed and dried to obtain the nano-metal bismuth particles.

3. The method for preparing the sandwich structure diaphragm coating material according to claim 1, characterized in that: The step of depositing carbon nanotubes on the nano-metal bismuth particles by vapor deposition includes the following process: The nano-metal bismuth particles are reacted at a temperature of 550-650° C. with acetylene as a carbon source for 1-2 hours, and then cooled to room temperature to obtain the Bi@CNT.

4. The method for preparing the sandwich structure diaphragm coating material according to claim 1, characterized in that: The step of loading aluminum oxide on the Bi@CNT by a hydrothermal synthesis method includes the following process: The Bi@CNT and aluminum chloride are added into water and stirred, and then hydrothermally synthesized at 180-250° C. for 8-10 hours. After the reaction is completed, the Bi@CNT is washed and dried to obtain aluminum oxide loaded on the Bi@CNT.

5. The method for preparing the sandwich structure diaphragm coating material according to claim 4, characterized in that: The weight ratio of the Bi@CNT to the aluminum chloride is (30-40):(60-80).

6. The method for preparing the sandwich structure diaphragm coating material according to claim 1, characterized in that: The steps of using the Bi@CNT-Al2O3 and polydopamine as raw materials and adopting a self-assembly method to prepare the sandwich structure diaphragm coating material include the following processes: The Bi@CNT-Al2O3 and the polydopamine are added into water and dispersed by stirring, so as to form the sandwich structure diaphragm coating material through self-assembly.

7. The method for preparing the sandwich structure diaphragm coating material according to claim 1, characterized in that: The weight ratio of the Bi@CNT-Al2O3 and the polydopamine is (60-80):(60-80).

8. A sandwich structure diaphragm coating material, characterized in that: The sandwich structure diaphragm coating material is prepared by the preparation method described in any one of claims 1 to 7.

9. Use of the sandwich structure diaphragm coating material obtained by the preparation method according to any one of claims 1 to 7 or the sandwich structure diaphragm coating material according to claim 8 in the preparation of lithium ion batteries.

10. A lithium ion battery, characterized in that: The battery diaphragm material of the lithium-ion battery comprises the sandwich structure diaphragm coating material obtained by the preparation method according to any one of claims 1 to 7 or the sandwich structure diaphragm coating material according to claim 8.